El Lissitzky’s Red Wedge as the Hebrew letter Yud - Kamczycki, Artur (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The analysis undertaken in this paper sets out with El Lissitzky’s 1919 revolutionary poster entitled Beat the Whites with the Red Wedge. This artwork, composed of simple geometric figures, in which an acute-angled red triangle splits the form of a white circle, was used by Soviet propaganda to affirm the so-called ‘October events’. However, a thorough analysis of the poster, i.e. its sources, inspirations, borrowings and contexts, supports the hypothesis that the principal motif (the wedge) also constitutes a graphic equivalent of a letter of the Hebrew alphabet, the letter yud, represented as a small comma or, significantly, an acute-angled triangle. Such a premise yields further consequences with regard to meanings, encompassing aspects related to the Jewish iconic tradition that involve mysticism, magic, and the kabbalah.